2023
DOI: 10.1088/1755-1315/1244/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Shear Capacity of Hollow Reinforced Concrete Members without Stirrups

R Thamrin,
SH Dewi,
A Asrianur
et al.

Abstract: This paper presents experimental results on the shear capacity of hollow reinforced concrete members without stirrups. The area of the hollow was 2.32% of the concrete cross-sectional area. The hollow size used in this study is smaller than the maximum percentage required in the code, where the maximum hollow area was 4% of the total cross-sectional area. The longitudinal reinforcement used in the specimen varies with the three types of reinforcement ratios. The test was carried out using the four-point shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This reference reported that the flexural capacity of specimens with closed spiral stirrups and hoops was almost the same, but the ductility of spiral hoops was slightly higher.Shear failure is a sudden collapse that must be anticipated because it is extremely dangerous due to its brittle and sudden occurrence. This premature failure is typically caused by insufficient crosssectional area and shear reinforcement to withstand shear, as well as other factors that reduce shear capacity.[12], [13], [14], and [15]. Due to changes made to the rules of the current seismic code,…”
mentioning
confidence: 99%
“…This reference reported that the flexural capacity of specimens with closed spiral stirrups and hoops was almost the same, but the ductility of spiral hoops was slightly higher.Shear failure is a sudden collapse that must be anticipated because it is extremely dangerous due to its brittle and sudden occurrence. This premature failure is typically caused by insufficient crosssectional area and shear reinforcement to withstand shear, as well as other factors that reduce shear capacity.[12], [13], [14], and [15]. Due to changes made to the rules of the current seismic code,…”
mentioning
confidence: 99%